2021
DOI: 10.1177/1356336x211036066
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and fidelity of Sport Education in Spanish schools

Abstract: The main objectives of this study were to determine the percentage of teachers applying the Sport Education (SE) model in a central region of Spain and to identify the features these teachers perceived they were using when applying it. As a secondary objective, an attempt was made to respond to the differences in the application of the model depending on the educational stage and gender, and to determine any differences between the curriculum features of teachers applying SE and those who follow other methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
4
0
3
Order By: Relevance
“…Recently, different studies have found that the implementation of this methodology can bring specific benefits for students such as social development and inclusion [27], content learning and development of responsibilities [28], intercultural understanding and friendship goals [29], or teamwork abilities [30]. Interestingly, a recent study indicated that, regardless of the adaptations that different teachers might make to implement the SEM, the use of this methodology can provide quality learning experiences to students [31]. The existing literature has also suggested that the implementation of the SEM in PE might lead to positive motivational outcomes, such as intrinsic motivation [32] or BPN satisfaction [21,33,34], even among those less intrinsically motivated students [35].…”
Section: The Sport Education Model's Characteristicsmentioning
confidence: 99%
“…Recently, different studies have found that the implementation of this methodology can bring specific benefits for students such as social development and inclusion [27], content learning and development of responsibilities [28], intercultural understanding and friendship goals [29], or teamwork abilities [30]. Interestingly, a recent study indicated that, regardless of the adaptations that different teachers might make to implement the SEM, the use of this methodology can provide quality learning experiences to students [31]. The existing literature has also suggested that the implementation of the SEM in PE might lead to positive motivational outcomes, such as intrinsic motivation [32] or BPN satisfaction [21,33,34], even among those less intrinsically motivated students [35].…”
Section: The Sport Education Model's Characteristicsmentioning
confidence: 99%
“…Investigaciones realizadas por estudiosos como Gutiérrez et al (2013), que utilizaron un modelo de Educación Deportiva nos corroboraron que los estudiantes de primaria y secundaria percibieron progresos en la NPB de competencia. Esto podría deberse a que el MED está diseñado originalmente para favorecer la práctica y el aprendizaje deportivo de los estudiantes (Siedentop, 1994), teniendo como base los resultados obtenidos en nuestra investigación se insta a implementar este tipo de investigaciones en grupos de escolares más extensos y con población ecuatoriana, puesto que, se evidencian resultados favorecedores en la satisfacción de las NPB en poblaciones con mayor masa y de nacionalidad española (García-López & Gutiérrez-Díaz, 2013) 154 estudiantes (Gutiérrez-Díaz et al, 2013), 270 entre niños y jóvenes.…”
Section: Resultados Y Discusiónunclassified
“…Investigaciones realizadas por estudiosos como Gutiérrez et al (2013), que utilizaron un modelo de Educación Deportiva nos corroboraron que los estudiantes de primaria y secundaria percibieron progresos en la NPB de competencia. Esto podría deberse a que el MED está diseñado originalmente para favorecer la práctica y el aprendizaje deportivo de los estudiantes (Siedentop, 1994), teniendo como base los resultados obtenidos en nuestra investigación se insta a implementar este tipo de investigaciones en grupos de escolares más extensos y con población ecuatoriana, puesto que, se evidencian resultados favorecedores en la satisfacción de las NPB en poblaciones con mayor masa y de nacionalidad española (García-López & Gutiérrez-Díaz, 2013) 154 estudiantes (Gutiérrez-Díaz et al, 2013), 270 entre niños y jóvenes.…”
Section: Resultados Y Discusiónunclassified